Perceived instrumentality value and engagement in 3D training, animation and modelling for university lecturers. (1st January 2012) - Gómez-Campos, Francisco M.; Amenyah, Efua Irene; Rodríguez-Bolívar, Salvador; Carceller, Juan E.; Frenay, Mariane; Bourgeois, Etienne
In this paper, authors report on an experience in adult education at the Universidad de Granada, Spain. They carry out an analysis on motivation and engagement of a group of university lecturers attending a training course on three-dimensional modelling and animation for teaching applications. They investigate the goals they are trying to achieve, their expectations and reasons for attending the course. Twenty-seven lecturers attended the course, including 53% of women and 47% of men. Results indicated that lecturers were motivated while attending the course. They engaged differently in the training course and were intrinsically focused on the content and importantly on new skills designed to be acquired. Fewer than three quarters (74%) finished the training course while others dropped out from the sessions very early or in the middle of the course due to unforeseen events.